Influence of TiO2/TS-1 Calcination on Hydroxylation of Phenol - Ediati, Ratna; Ulfa, Maria; Fansuri, Hamzah; Ramli, Zainab; Nur, Hadi; Prasetyoko, Didik (Journal of Mathematical and Fundamental Sciences, 2014)
Titanium oxide (TiO2) was impregnated on the surface of titanosilicate-1 (TiO2/TS-1) and used as catalyst for hydroxylation of phenol with hydrogen peroxide. Calcination was conducted at various temperatures (400, 500, 600 and 700°C)in order to observe the effect on the structure and physicochemical properties towards catalytic activity for producing hydroquinone. The structure and physicochemical properties of the TiO2/TS-1 catalyst were characterized by several techniques, such as X-ray diffraction (XRD), infrared spectroscopy, nitrogen adsorption, pyridine adsorption and hydrophilic measurement. The results show that by increasing the calcination temperature,the surface acidity of the catalyst was also increased.TheTiO2/TS-1 catalyst calcined at 500°Cproved to be optimal for hydroquinone production, in which the anatase-rutile phase may be present dispersed on the MFI framework.